Teacher’s Islamic Communication Strategy in Character Education through Parenting Program at SDIT Al Fityan Medan School - Sikumbang, Ahmad Tamrin; Lubis, Lahmuddin; Hasibuan, Effiati Juliana (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The main character education is not only the responsibility of teachers at school, but also must be a concern of parents at home. For this reason teachers need to convey the importance of character education for all of students’ parents through parenting programs. This study aims to describe how the character education communication strategy through parenting programs will be reviewed by students’ parents from the aspects of communication planning, program implementation and program evaluation also. This research uses a descriptive method with a qualitative approach. The data collection techniques uses participant observation and focus on  interviews. The technique of guaranteeing the validity of the data uses source triangulation. The results showed that the character education of students through parenting programs organized by schools in the aspects of planning, implementation and evaluation of the program was good enough. Parents have the benefits from this parenting program in educating their children at home.